Intervention for Children with Dyslexia in Chinese: A Comparison of Two Instructional Approaches - Luk, Sau Ha (ProQuest Dissertations & Theses, 2011)
This study evaluated the effectiveness of two supplemental intervention programs for children with Dyslexia in Chinese. Twenty-two children (mean age: eight years and four months) who were formally diagnosed with dyslexia were assigned to one of the two theoretically different reading interventions. Children in the Code-Emphasis program received explicit and systematic instructions in character recognition with meta-linguistic analysis (ortho-morphological and ortho-phonological awareness), fluency and reading comprehension. Children in the Meaning-Emphasis program received explicit and systematic instructions on vocabulary building, fluency and comprehension. Both groups received 25 two-hour sessions (i.e., 50 hours in total) of intervention led by the researcher and teaching assistants for five consecutive weeks in the summer when the children did not attend regular classes. Pre- and post-intervention performances were measured in terms of (1) Reading Achievement Measures: Character Dictation (Spelling), Character Reading Fluency Test, Passage Reading Fluency Test and Reading Comprehension Test, and (2) Meta-Linguistic Measures: Test of Logographic Principles and Test of Orthographic Structure (Copying Accuracy Test and Copying Fluency Test). In the course of the intervention, students' progress was monitored eight times by measuring the students' character and passage reading fluency. Results indicate that (a) Meaning-Emphasis students demonstrated greater gains over the comparison group at the end of the 50-hour intervention on measure of Passage Reading Fluency Test after adjusting pre-intervention differences; (b) Code-Emphasis students showed an advantage over the comparison group on Copying Fluency Test after adjusting pre-intervention differences; (c) for the pre-post within group intervention effect, there were large treatment effects for four tests (Character Reading Fluency, Passage Reading Fluency, Dictation and Reading Comprehension Test) in the Code-Emphasis group, whereas Meaning-Emphasis group, there were two tests (Character Reading Fluency and Passage Reading Fluency) with large within group treatment effect and two tests (Dictation and the Test of Logographic Principle) reflected medium treatment effect, and for the comparison group, only the test of reading comprehension reached large effect; and (d) coorelational and regression analyses showed that meta-linguistic awareness of the features of Chinese orthography is highly related to literacy achievement. Implications for future research and practice of supplementary Chinese literacy interventions in Hong Kong for children with dyslexia are discussed.